2021
DOI: 10.1101/2021.03.29.21254546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Food Insecurity in the Households of Children with Autism Spectrum Disorders and Intellectual Disabilities in the U.S.: Analysis of the National Survey of Children’s Health Data 2016 - 2018

Abstract: Individuals with Autism Spectrum Disorder and co-occurring Intellectual Disabilities (ASD + ID) experience substantial challenges in accessing needed supports. This research aimed to understand the prevalence and factors associated with food insecurity among families of children with ASD + ID. Utilizing the National Survey of Childrens Health (2016-18) data, this paper illustrated that the households of children with ASD + ID were about two times more likely to be food insecure than the households of children … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…1 People with disabilities and households of individuals with autism spectrum disorder (ASD) were at a greater risk for food insecurity when compared to the general population. 2,3 Studies have demonstrated the short- and long-term physical and mental health impacts of food insecurity. 4 According to the US Census Bureau’s Household Pulse Survey (which asks how the coronavirus pandemic is impacting households), 18.3% of households with children experienced food insufficiency in the last seven days.…”
Section: Introductionmentioning
confidence: 99%
“…1 People with disabilities and households of individuals with autism spectrum disorder (ASD) were at a greater risk for food insecurity when compared to the general population. 2,3 Studies have demonstrated the short- and long-term physical and mental health impacts of food insecurity. 4 According to the US Census Bureau’s Household Pulse Survey (which asks how the coronavirus pandemic is impacting households), 18.3% of households with children experienced food insufficiency in the last seven days.…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity is strongly related to economic and social factors that contribute to systems of oppression, including unemployment, poverty, disability, and race and ethnicity (Odoms-Young & Bruce, 2018). Children with disabilities, such as those NCC serves, are also more likely to experience low or very low food security than children without disabilities (Karpur et al, 2021). With the partnership of staff and community members at NCC, our team developed the Health and Nutrition Initiative to educate families of young children about the link between nutrition and health, featuring increased attention on IDD in an inclusive setting.…”
Section: National Children's Centermentioning
confidence: 99%